Artemis Fowl. The last guardian [compact disc, unabridged] - Colfer, Eoin (Colfer, Eoin. Artemis Fowl (Sound recording), 2012)
Artemis's arch rival Opal Koboi has reanimated dead fairy warriors that take possession of Artemis's little brothers. Artemis has until sunrise to get the spirits to vacate his brothers and go back into the earth where they belong.